2018
DOI: 10.1016/j.isci.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying MnVII-oxo Species during Electrochemical Water Oxidation by Manganese Oxide

Abstract: SummaryIdentifying surface active intermediate species is essential to reveal the catalytic mechanism of water oxidation by metal-oxides-based catalysts and to develop more efficient catalysts for oxygen-oxygen bond formation. Here we report, through electrochemical methods and ex situ infrared spectroscopy, the identification of a MnVII = O intermediate during catalytic water oxidation by a c-disordered δ-MnOx with an onset-potential-dependent reduction peak at 0.93 V and an infrared peak at 912 cm−1. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 32 publications
0
47
0
1
Order By: Relevance
“…43 Very recently, we reported the presence of an essential Mn VII -dioxo intermediate in a synthetic c-disordered δ-MnO xbased water oxidation catalyst (i.e., MnO x -300), 45 where a Mn IV -O-Mn VII vO was proposed as the active species for O-O bond formation. 44 As shown in Fig. 4 , which is unique, i.e., distinguishable from other 3 Mn ions by being placed outside the cubane structure.…”
Section: Proposing the Mn VII Species Involved Mechanismmentioning
confidence: 95%
“…43 Very recently, we reported the presence of an essential Mn VII -dioxo intermediate in a synthetic c-disordered δ-MnO xbased water oxidation catalyst (i.e., MnO x -300), 45 where a Mn IV -O-Mn VII vO was proposed as the active species for O-O bond formation. 44 As shown in Fig. 4 , which is unique, i.e., distinguishable from other 3 Mn ions by being placed outside the cubane structure.…”
Section: Proposing the Mn VII Species Involved Mechanismmentioning
confidence: 95%
“…By forming MnN bonds through the introduction of nitrogen ligands on the MnO 2 surface, Mn(III) species were stabilized by suppressing the CD reaction, thus leading to the OER activity enhancement . Recently, there have been some insightful studies on the Mn based water oxidation catalysts regarding the mechanistic studies including OO bond formation and identification of Mn VII O intermediate during catalytic water oxidation, structural and electronic effects on superior OER activity of activated‐MnO 2 and the correlation between the stability of the intermediate species and crystal facet …”
Section: Introductionmentioning
confidence: 99%
“…The two DFT structures exhibited in Figure 2b couldb ee asily interconverted under certain conditions, as demonstrated through DFT calculations. [53] Considering the high catalytic activitya nd stability,m ultinuclear Mn 12 DH [23] and mononuclear Mn-NG, [14] which exhibit excellent performances, have been synthesized.W OCs with low overpotential, high TOF (Table 1), and strong durability can bring some new insightsi nto the preparation of increasingly efficient catalysts for the OER. EPR spectroscopy can be used to monitor the catalytic process, and every Ss tate has itso wn EPR signal.…”
Section: Manganese-based Wocsmentioning
confidence: 99%
“…The redox potentials of [Mn 4 CaO 4 (tBuCO2) 8 (tBuCO 2 H) 2 (py)] were different from those of the Mn 3 CaO 4 complex, [7] which indicated that the fourth Mn could change the redox potential. [53] The following formation process for the active inter- [53] The following formation process for the active inter- …”
Section: Trinuclear Manganese-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation